Effect of Irrigation Solution Temperature on Complication of Percutaneous Nephrolithotomy: A Randomized Clinical Trial - Hosseini, Seyed Reza; Mohseni, Mohammad Ghasem; Aghamir, Seyed Mohammad Kazem; Rezaei, Hamed (Urology Journal, 2019)
Purpose: Many factors affecthypothermia and shivering during percutaneous nephrolithotomy and in recovery. Hence this study was carried out to determine the effect of irrigation solution temperature on complications of percutaneous nephrolithotomy. Materials and Methods: In this randomized clinical trial, 60 patients undergoing PCNL in Sina University Hospital were enrolled. The patients were randomly assigned in three groups according to simple random manner. The groups included three groups of room temperature fluid (24 degree), warm solution (37 degree), and cold fluid (20 degree) during nephroscopy. Results: Although the initial core temperature was alike across the groups (P > .05); the hypothermia rate occured in all 20 patients in the cold fluid group (P = .012). There was significant difference between the groups in terms of final temperature and alteration amount (P = .001). The mean VAS scores were significantly lower in the warm fluid group compared with the others groups at recovery, and 8hrs post-operatively (P = .03). Assessment of shivering rates revealed that 3(15%) patients in warm solution group shivered compared to8 (40%) patients in cold fluid group (P = .018). Conclusion: Warm irrigation solution during PCNL results in significantly decreased hypothermia, mean postoperative pain score and shivering. Hence use of warm irrigation fluid for this matter is recommended.